2014
DOI: 10.1111/odi.12286
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus in the oral cavities of persons with Fanconi anemia

Abstract: Objective We conducted a cross-sectional study to describe the prevalence and correlates of type-specific human papillomavirus DNA in the oral cavities of persons with Fanconi Anemia. Materials and Methods Oral swabs were collected from 67 participants with Fanconi Anemia and tested for 27 human papillomavirus genotypes using polymerase chain reaction-based methods. Results Participants were a mean of 18.6 (standard deviation, 10.0) years of age (range 4 to 47 years). The prevalence of oral human papilloma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
2
9
1
Order By: Relevance
“…In this case series study, 28% of the FA patients admitted to an HSCT reference center had HPV detected in the oral mucosa, which is higher than estimates from other studies with FA patients and also higher than estimates from studies with the general population, 7.5% to 11.1% and 6.9%, respectively …”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In this case series study, 28% of the FA patients admitted to an HSCT reference center had HPV detected in the oral mucosa, which is higher than estimates from other studies with FA patients and also higher than estimates from studies with the general population, 7.5% to 11.1% and 6.9%, respectively …”
Section: Discussioncontrasting
confidence: 71%
“…Lowy and Gillison suggested that the period between HPV infection and the development of cancer may be considerably shorter in FA patients, which could explain the occurrence of head and neck SCC (HNSCC) or vulvar cancer in relatively young FA patients. While some studies have failed to detect HPV DNA in HNSCC and anogenital SCC samples from subjects with FA, some epidemiological studies continue to provide evidence of risk …”
Section: Introductionmentioning
confidence: 99%
“…It is plausible, although speculative, that less common high-risk types, or even low-risk HPV types, might unusually initiate a cancer cascade in those with FA who have both a DNA repair defect and heterogeneous immune deficiency, suggesting a need to evaluate the broad spectrum of HPV types rather than HPV16 and 18 alone in oral rinse and possibly other sample types. Indeed, among 67 throat swabs from individuals with FA collected at the same time as our oral rinse samples in this report, we identified 5 individuals positive for HPV 33, HPV 84, HPV 66, 51, 52, 62 82 and HPV 51; a 60% agreement between sample types (32). …”
Section: Discussionmentioning
confidence: 68%
“…Recently, the prevalence of oral HPV infection in patients with FA (and without OPSCC) was assessed and the results were found to be similar to studies of the general population, with the prevalence of oral HPV being 7.5 % (Winer et al 2015). The prevalence of high-risk HPVinfection was 6 %, but oral HPV16 was not observed.…”
Section: The Prevalence Of Hpv Infectionmentioning
confidence: 83%